2019
DOI: 10.1007/s11240-019-01701-8
|View full text |Cite
|
Sign up to set email alerts
|

In vitro induction of auto-allotetraploid in a newly developed wild rice line from Oryza alta Swallen

Abstract: Oryza alta Swallen is an important germplasm for rice resistance breeding; however, its CCDD genome (2n = 48) resulted in low crossability when the wild rice was crossed with O. sativa and restricted the success of transferring the desirable traits into cultivated rice. Induction of polyploidy is an efficient way for overcoming the low crossability among different species. A new O. alta line, Huaye 5, was developed by our group in 2016, which had high fertility (64.93%) and photoperiod-insensitive. Huaye 5 was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 48 publications
1
11
0
Order By: Relevance
“…According to the age and outcomes of cytogenetics and karyotype, WGD events can be classified into two kinds, one is the recent or new polyploidization event, which results in "autopolyploids" and emerge from the fusion of gametes produced by non-meiosis, or hybridization of normal meiosis gametes of same species individuals, or "allopolyploids" produced from inter-specific hybridization [18]. About 47-70% of angiosperm species are estimated as polyploid and approximately 25% of vascular plants have undergone recent polyploidization [19,20], and this WGD event could be detected by karyotyping and flow cytometry method [21]. Another is the ancient polyploidization event, which happened in earlier geological ages.…”
Section: Introductionmentioning
confidence: 99%
“…According to the age and outcomes of cytogenetics and karyotype, WGD events can be classified into two kinds, one is the recent or new polyploidization event, which results in "autopolyploids" and emerge from the fusion of gametes produced by non-meiosis, or hybridization of normal meiosis gametes of same species individuals, or "allopolyploids" produced from inter-specific hybridization [18]. About 47-70% of angiosperm species are estimated as polyploid and approximately 25% of vascular plants have undergone recent polyploidization [19,20], and this WGD event could be detected by karyotyping and flow cytometry method [21]. Another is the ancient polyploidization event, which happened in earlier geological ages.…”
Section: Introductionmentioning
confidence: 99%
“…The genetic transformation of several wild Oryza accessions had been reported, however, its regeneration and transformation efficiency were low ( Zhang et al, 2019 ; Shimizu-Sato et al, 2020 ; Yu et al, 2021 ). An efficient genetic transformation system for wild rice is needed to be well established.…”
Section: Discussionmentioning
confidence: 99%
“…Allotetraploid Oryza alta Swallen with CCDD genome from South America, possesses a variety of disease and insect resistances ( Mao et al, 1995 ; Ammiraju et al, 2010 ). The tissue culture study of Swallen showed that the callus induction rate and regeneration frequencies were only 20 and 10%, respectively ( Zhang et al, 2019 ), suggesting that its callus induction and regeneration ability were extremely low. Polyploid rice 1 (PPR1) from South America is also an allotetraploid wild rice with CCDD genome.…”
Section: Introductionmentioning
confidence: 99%
“…Rice improvements help us to meet the challenge of feeding a population by breeding better varieties as fast as we can. However, with the continuous growth of the world’s population and the continuous development of the economy ( Zhang et al., 2019 ), the requirements for the quality of human life have risen sharply. Moreover, decreased relative arable land area ( Fei et al., 2018 ; Xie et al., 2018 ; Li et al., 2021 ) and deteriorated ecological environment ( Jiang et al., 2021 ; Zhou et al., 2021 ) made rice food scarcity prominent ( Guo et al., 2022 ), which attracted attention from all walks of life.…”
Section: Introductionmentioning
confidence: 99%
“…Our previous research developed a new germplasm, Huaye 5, from O. alta , and established a protocol for in vitro induction of an auto-allotetraploid line ( Zhang et al., 2019 ). Huaye 5 is an important wild rice germplasm harboring many elite genes.…”
Section: Introductionmentioning
confidence: 99%